Water Quality Studies in Malacca River Basin Using Geographic Information Systems (GIS) - Lion Bayuhan, Marryanna Lion (2003)
Malacca Straits is recognized worldwide due to its importance as the busiest waterway in the world. The environmental profile of the Malacca Straits points to certain stresses in the ecosystem due to pollution load. Pollutants from land-based sources are probably the most pressing environmental problem. Wastes from agricultural, industrial, and domestic source discharge directly into the Straits or indirectly via rivers, which flow into the Straits. As far as land based pollution is concerned, study on river basin is important. The Malacca River basin is of the rivers flowing into the Straits of Malacca. Geographic information System (GIS) was used to map the water pollution scenario due to its ability to analyze spatial and temporal data. Beside that, correlation coefficient method was used to determine the relationship and variation between rainfall and water quality parameters. Six parameters selected for this study. namely. Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Ammoniacal Nitrogen. pH, Suspended Solid (SS), and Dissolved Oxygen (DO). The output of this study consists of water quality database. maps, and graphs on the water quality variations. The important of this study is the application of GIS technology in monitoring water quality. Technology plays an important role for effective environmental management.